Acute beetroot juice supplementation improves exercise tolerance and cycling efficiency in adults with obesity. Issue 19 (14th October 2020) - Behrens, Christian E.; Ahmed, Khandaker; Ricart, Karina; Linder, Braxton; Fernández, José; Bertrand, Brenda; Patel, Rakesh P.; Fisher, Gordon
Abstract: Background: Exercise training improves health outcomes in individuals with obesity (IO); however, it remains challenging for IO to adhere to exercise. Thus, it is critical to identify novel strategies that improve exercise tolerance (ET) and adherence in IO. Beetroot juice (BRJ), high in inorganic dietary nitrate, consistently improves exercise performance in athletes, individuals with cardiopulmonary diseases, and nonobese lean individuals. These improvements may be explained by reduced oxygen uptake (VO2 ) during exercise, enhanced blood flow, and greater mitochondrial efficiency. To date, we are aware of no studies that have compared the effects of BRJ, sodium nitrate (NaNO3), and nitrate‐depleted BRJ (PLA) for improving ET and cardiometabolic health in IO. Purpose: Determine if BRJ improves ET, exercise efficiency (EE), and cardiometabolic health in IO and identify possible mechanisms of action. Methods: Vascular hemodynamic, submaximal‐ and maximal‐exercise VO2, and time to exhaustion (TTE) were assessed in 16 participants 2.5 hr following consumption of: 1) BRJ, 2) NaNO3, 3) PLA, or 4) CON. Results: A significant treatment effect was observed for submaximal exercise VO2 ( p  = .003), and TTE ( p  < .001). Post hoc analyses revealed lower VO2 during submaximal exercise in BRJ compared to PLA ( p  = .009) NaNO3 ( p  = .042) and CON (0.009), equating to an average improvement of ~ 7% with BRJ. TTE was greater for BRJ compared to other treatment arms, PLA ( p  = .008), NaNO3 ( p  = .038), and CON ( p =<0.001), equating to ~ 15% improvement with BRJ. No significant changes were observed for other outcomes. Conclusions: Consumption of BRJ improved EE during submaximal exercise by 7%, and TTE by 15% compared to other conditions. These results suggest that BRJ may improve EE and exercise tolerance in IO. Abstract : Exercise training improves health outcomes in individuals with obesity, however it remains challenging for individuals with obesity to adhere to exercise. Evidence suggests beetroot supplementation improves exercise‐related outcomes in athletes and the non‐obese lean, however the crossover of these effects onto adults with obesity is not clear. This study primarily aimed to determine if beetroot juice improves exercise tolerance and efficiency in individuals with obesity. Supplementation with beetroot juice significantly reduced oxygen uptake during submaximal exercise (~7%), and increased by ~9% during severe‐intensity exercise. Perhaps most notable was a ~22% improvement in time to exhaustion observed following beetroot juice intake compared to control. Taken together acute supplementation with BRJ may be effective for improving exercise tolerance and efficiency in individuals with obesity.